The eírōn/alazṓn Dynamic and New Testament Studies: The Case of the Tractatus Coislinianus - Pawlak, Matthew (Zeitschrift für die neutestamentliche Wissenschaft, 2025)
New Testament scholars discussing irony have for decades invoked a character dynamic from Greek Old Comedy between the εἴρων and the ἀλαζών, the dissembler and the braggart, to explain the relationship between different characters in the Gospels and Paul’s letters. This article investigates the validity of this dynamic by analyzing its source: The Tractatus Coislinianus , a 10 th century manuscript that claims to summarize Aristotle’s lost work on comedy ( Poetics II ). The article uses Aristotle, including Poetics I , Rhetoric , and the Nicomachean Ethics , in addition to Old Comedy and Cicero to determine the likelihood that the εἴρων/ἀλαζών dynamic has its roots in Aristotelean thought and Old Comedy as described in the tractatus and argued in scholarship.